Synthesis and Characterization of Nano-sized Carbonated Calcium Hydroxyapatite (CHAp) from Rebon shrimp (Acetes erythraeus) as a Candidate for Dental Restoring Application - Ngatijo Ngatijo; Restina Bemis; Heriyanti Heriyanti; Rahmi Rahmi; Nashih Ulwan; Rahmat Basuki (Jurnal Kimia Valensi, 2021)
Carbonated calcium hydroxyapatite (CHAp) exhibits excellent biocompatibility with bone and teeth, making it an ideal candidate for orthopedic and dental application. However, the study of CHAp synthesis from natural material is still scarce. The purpose of this research is to synthesize and characterize of CHAp, using Rebon shrimp (Acetes erythraeus) as a calcium source. The synthesis was conducted by hydrothermal method with the variation of Ca/P ratios 1.61; 1.67; 1.73. The as-prepared CHAp was characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and scanning electron microscopy-energy dispersive X-ray (SEM-EDX). The FT-IR results show that synthesized material exhibited characteristic CHAp band of hydroxide at 3448 and 1635 cm-1, carbonate at 872 and 1427 cm-1, and phosphate at 1049; 606; and 570 cm-1. The diffractogram pattern assigned the all observed peak of CHAp are in good agreement compared to CHAp database with the nano-scale size. It also observed that the high Ca/P ratio will decrease the crystallinity of CHAp. The as-prepared CHAp micrograph is agglomerates spherical form with size between 5-20 nm which build up from 18–26 nm crystallite particles. The result of this research confirmed that Rebon shrimp is the promising materials for calcium source in CHAp production.